'If It Wasn't For Us … ': Peripheral Narratives of the Pacific War. Issue 1 (2nd January 2022) - Di Rosa, Dario
ABSTRACT: Scholarship on the Indigenous experience of World War II has justly focused on recording accounts of direct witnesses of that period. Such a sense of urgency, at least in Papua New Guinea, has led to the neglect of areas of the country that, though not directly affected by the war, were invested in the war effort by providing labour and soldiers. Communities residing in those areas recall stories of their war heroes as key figures for the liberation of the country and, ultimately, its current adherence to 'Western values'. Through an analysis of the moral claims that those peripheral stories entail, in this article I suggest potential directions for the study of narratives of World War II that move beyond 'the era of the witness'.